2020
DOI: 10.5507/tots.2020.011
|View full text |Cite
|
Sign up to set email alerts
|

Driving and tiredness: Results of the behaviour observation of a simulator study with special focus on automated driving

Abstract: Driving and tiredness: Results of the behaviour observation of a simulator study with special focus on automated driving systems that assume a driver as emergency fallback. Further research is recommended to investigate safe modes of control hand over in automated driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This figure also shows that even in the rested condition, some drivers showed signs of moderately and extremely drowsy states. More details of the ground truth definition for driver drowsiness using video observations are explained in our previous publication [30].…”
Section: Ground Truth Definition For Driver Drowsinessmentioning
confidence: 99%
“…This figure also shows that even in the rested condition, some drivers showed signs of moderately and extremely drowsy states. More details of the ground truth definition for driver drowsiness using video observations are explained in our previous publication [30].…”
Section: Ground Truth Definition For Driver Drowsinessmentioning
confidence: 99%
“…This Figure also shows that even in the rested condition, some drivers showed signs of moderately and extremely drowsy states. More details of the ground truth definition have been explained in a previous publication [24].…”
Section: Ground Truth Definition For Driver Drowsinessmentioning
confidence: 99%
“…Furthermore, 14.5% of the drivers in the USA have been involved in at least one drowsiness-related traffic collision, according to a study carried out in 2008 8 . Some studies also showed that the level of drowsiness in automated driving is significantly higher than in manual driving [10][11][12] . Given all this evidence, the estimation of driver fatigue is essential for road safety and also future intelligent transportation systems require a vigilant driver for take-over requests from automated vehicles failing to perform safely.Generally, three types of data have been used in the literature to design driver drowsiness detection systems: (1) vehicle-based 13,14 , (2) vision-based 15,16 , and (3) physiological data 17,18 .…”
mentioning
confidence: 99%